Gerenciamento de crises ocasionadas por influenciadores digitais: um estudo do posicionamento das marcas - Lourenço, Tamíris Andressa Sbrissa (Universidade Federal de São Carlos, 2020)
With the intensification of the use of social media, many companies have used digital influencers to disseminate their brands. However, in recent years there has been an increase in crises caused by these professionals, generating moments of discomfort for brands. Because of this, this article focused on analyzing how companies that hire digital influencers position themselves in the face of crises caused by them, in addition to assessing how the public judges such positioning. The results of the research showed that the companies carried out similar positions and that these positions resulted in different impacts on the public, being possible to classify the opinion in: Manifestation of Positive Support, Manifestation of Loyalty, Manifestation of Purchase Intention and Manifestation of Cancellation.
Crisis management occasioned by digital influencers: a study of brand positioning
Keywords: Influenciadores Digitais; Gerenciamento de Crises; Mídias Sociais; Comunicação Empresarial; Reputação da Marca; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::MERCADOLOGIA